Representation of a `positive experience' of surrogacy in Yazd, Iran: A qualitative study - Zahra Ghane-Mokhallesouni; Abbas Askari-Nodoushan; Hajieh Bibi Razeghi Nasrabad; Ahmad Kalateh Sadati; Razieh Dehghani Firouzabadi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The social and cultural challenges facing surrogate mothers have been explored in several studies. However, few studies have discussed the motivations of surrogate mothers, their expressions and interpretations of their lived experiences, and their feelings of personal and spiritual satisfaction. Objective: This study aims to present the positive experiences of surrogate mothers from a phenomenological perspective. Materials and Methods: Using a phenomenological approach, this study was conducted from September 2020 to January 2021 in the city of Yazd, Iran. Participant observation and semi-structured interviews were used to collect the data among 12 participants with at least 1 experience of surrogate motherhood. Results: Our findings showed that, despite having had harsh physical and socio-cultural experiences such as fear of social labeling and stigma, participants felt a kind of inner satisfaction and a positive view of their actions. A core theme found in the study was mothers' satisfaction. The main categories included feminine self-sacrifice and positive rewards. Feminine self-sacrifice included 2 sub-categories: creating happiness and conveying motherly feelings, while positive rewards included good childbirth, family acceptance, and halal income. Conclusion: This study showed that surrogate mothers experience conflicting feelings of inner satisfaction and social stigma during surrogacy. Some of those interviewed were willing to go through surrogacy again, but they feared social labeling and stigma, being misunderstood by others who are not fully informed about surrogacy, and being subjected to family and social disapproval.